STUDY OF THE USE OF MANGOSTEEN PEEL ECO-ENZYME FOR PRESERVING EGGS BASED ON ENVIRONMENTALLY FRIENDLY TECHNOLOGY - Siswara, Hamzah Nata; Rachmawati, Laila Dian; Rozi, Fachrul; Nurenik, Nurenik; Huda, Khoirul (Unpad Press, 2026)
Egg quality decreases during storage due to evaporation of air and gas from the egg and microbiological damage. This study aims to increase the shelf life of eggs using eco-enzymes from mangosteen peel. The benefits that can be obtained from this study are providing a solution for the community in extending the shelf life of eggs and can utilize environmentally friendly technology through the utilization of organic waste. The research procedure includes the stages of making eco-enzymes from mangosteen peel, eco-enzyme screening tests, egg sample selection, egg coating stages, and egg quality testing stages. Meanwhile, research variables include environmental temperature and humidity, difference in egg weight shrinkage, shell weight, shell thickness, air cavity, egg white index (IPT), egg yolk index (IPT), Haugh unit (HU), egg white and yolk pH values, and egg white and yolk moisture. Phytochemical testing shows that mangosteen peel ecoenzymes have phytochemical content suitable for preservation. Includes flavonoids, tannins, saponins, and alkaloids. The physicochemical characteristics of eggs after storage showed that the addition of mangosteen rind eco-enzyme had a significant effect (P<0.05) on the characteristics of egg whites and yolks. Eco-enzyme has the potential to be an environmentally friendly natural preservative for eggs during storage.